Managing the Merchandise Planning Process in SME - Rasyid, Ardiansyah; Glacio, Rich; Meiwinka, Meiwinka; Fernando, Luis (Transpublika Publisher, 2024)
The training on managing the merchandise planning process in Jamu (herbal drink) SMEs aims to enhance the skills and knowledge of SME practitioners in the herbal drink sector in planning merchandise effectively. This training covers the basic understanding of merchandise planning, market demand analysis, inventory management, procurement techniques, and the use of technology in planning. Additionally, the training includes case studies and simulations to provide practical experience, as well as explanations on the importance of evaluation and monitoring in the planning process. Through this training, herbal drink SME practitioners are expected to manage their merchandise more efficiently, thereby improving operational efficiency and competitiveness in the market.